p-Dimethylaminobenzaldehyde: preliminary investigations into a novel reagent for the detection of latent fingermarks on paper surfaces - Lewis, Simon; Fritz, Patrick; Van Bronswijk, Wilhelm (R S C Publications, 2013)
A new method for the detection of latent fingermarks on paper surfaces using p-dimethylaminobenzaldehyde (DMAB) is described. The method is based upon the reaction of DMAB with the amino acids present in the latent fingermark to give a yellow-brown impression that is photoluminescent when illuminated with a high intensity filtered light source at 490 nm and viewed through orange goggles (OG550). A wet contact method proved effective on non-fragile porous substrates such as white photocopy paper and various other substrates, while a dry contact (solventless) method afforded development on thermal paper. Luminescence spectrophotometry of developed L-alanine, glycine and L-serine spots on paper was used to confirm that DMAB was reacting with amino acids in the latent fingermark.